Emílias e pinóquios: um olhar pedagógico sobre o entrelaçamento do sexismo, gênero e sexualidade nos modos de aprender a ser mulher e a ser homem - Santos, Anelise Dutra (Universidade do Vale do Rio do Sinos, 2005)
This reseach had as one of the purpose to analyse through deposition of women-teachers, configurations about sexuality at school as well as enlarge the universe to debates/equality searching and stimulating a construction/disorder of human beings, diferent from the social and cultural representation established in sexist speeches refering through the patriarchal logic. The work had through the hystorical rescue about women and their narrative with the intention of turning our problematic formation through: family, school and church, influencing our behavior, attitudes in our way of being a woman and a man, because before being a teacher we were girls, women, daughters, mothers and without any daughts there is a distinct look over the constitution of being a boy, man, son and father. It´s also important to say that the base of investigation were the narrative and the images of fairy tales were the support to notice the cultural construction of sexist gender. This means, the three movements, the narratives, the
Keywords: diferença sexual; educação infantil; escola; gênero; orientação sexual; sexismo; educação sexual; education; feminism; gender; patriarcalism; sexism; sexuality; Ciências Humanas